Quality of Public Services in Housing and Settlement Environments in Maluku Province - Sahetapy, Petronela; Lopulalan, Dortje L J (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The purpose of this study was to analyze the quality of civil service at the Maluku Province Housing and Settlement Service. Qualitative methods were used to produce a more comprehensive study of a phenomenon on the subject of the study. The results of the study showed1. various obstacles were encountered such as being slow in carrying out reports and not according to the targeted time. 2. the motivation aspect, needs to be improved because it affects the completion of work or tasks and responsibilities given.. 3. the knowledge aspect, as an initiative taker related to thinking power, creativity in the form of ideas to plan something related to organizational goals is not yet adequate.. 4. Leadership aspects in the team, encouraging work morale and creating a better work culture. . Constructive recommendations are seen from the aspect of initiative and problem solving that are not yet adequate so that a good employee mentality is needed in building self-confidence by giving tasks and responsibilities to employees and creating a positive work culture and ensuring that a good communication system can be built so that a comfortable work environment is created and implementing a reward and punishment system in carrying out the tasks given so that the organization's goals are in line with the targets that have been set.